The Superficial Musculoaponeurotic System Facelift: A Prudent Balance of Risks and Benefits - McCollough, E. Gaylon (Facial Plastic Surgery, 2017)
Over the decades, facelifting has not escaped the natural history of trends and fads. And, as a profession, facial plastic surgery has not avoided falling into the trap of following corporate initiated technology, rather than leading common-sense methodologies to rejuvenating the aging face. The author is often reminded of a truism to which he was introduced in the 1980s. “When there are many ways of doing things, all of them work; or none of them work.” Undeniably, any procedure that lifts and removes excessive skin of the face and neck “works.” However, the questions that must be answered by leading teachers of facelifting surgery are: How well does a given technique work? How long-lasting are the results? Where does the risk–benefit curve cross over from optimal benefits to unacceptable risks? At what stage in a given patient's aging process are more aggressive techniques called for? At what stage in a surgeon's career should more invasive techniques be attempted, if ever? This article addresses the preceding questions as they relate to the contribution made by the superficial musculoaponeurotic fascia in repositioning sagging tissues of the face and neck.
Keywords: condition-specific facelift; SMAS suspension; facial rejuvenation